Building blocks of human design thinking in animals. Issue 1 (3rd April 2017) - Dong, Andy; Collier-Baker, Emma; Suddendorf, Thomas
Abstract : Observations of animal innovations range from tool making by chimpanzees to elaborately decorated nests made by bowerbirds. Such behaviors raise fundamental questions about the differences between human design thinking and the capacity of nonhuman animals to create novel objects and environments. While none of these animal innovations are based upon what we would describe as design thinking, elements of the cognitive skills that make up design thinking may exist in other species, even if they do not exist as a complete package or to the same degree of skill as in humans. Animal innovations thus provide a unique window into human design thinking. Using a comparative approach, we discuss three cognitive skills that are likely to be fundamental to the conceptual system of human design thinking: recursion, representation, and curiosity. There is evidence of two of these capacities in nonhuman animals.